Examining the Correlation between Smartphone Addiction and Leisure Boredom Perception in Ice Hockey Players - Muharrem Alparslan Kurudirek; Muhammet Irfan Kurudirek; Muhammet Irfan Kurudirek (Journal of Educational Issues, 2024)
The purpose of this study was to determine smartphone addiction and leisure boredom perception levels in ice hockey players in Turkey, examine them in terms of age, sex and educational level, and investigate the correlation between smartphone addiction and leisure boredom perception. The population of the study consisted of athletes actively playing in ice hockey leagues in Turkey. The sample group comprised a total of 85 athletes (51 males and 34 females) who were selected randomly from the population and were voluntary to participate in the study. In the study, a questionnaire with three sections was used as the data collection tool. The first section of the questionnaire was a personal information form prepared by the researcher to determine the age, sex, and educational background of the participants. In the second section of the questionnaire, the Smartphone Addiction Scale-Short Version (SAS-SV) was used for measuring the smartphone addiction levels of the participants. In the third and last section of the questionnaire, the Leisure Boredom Scale (LBS) was used for determining the leisure boredom perception of the participants. In the data assessment, the SPSS 26 package software was used. After transferring the data collected via the data collection tool into the electronic environment, the normality was first tested and then non-parametric analyses were performed upon detecting that the data were not normally distributed. When examining the findings of the study, it was observed that most of the participants were male, had high school education and below and were aged 15 to 17 years. In addition, the mean scores of the participants were higher in the Leisure Boredom Scale Boredom Subscale, moderate in the Leisure Boredom Scale Satisfaction Subscale and higher in the Smartphone Addiction Scale-Short Version. It was determined that the female participants had higher mean ranks in the Leisure Boredom Scale Boredom Subscale compared to the male participants at a statistically significant level. When examining the correlation between the smartphone addiction and leisure boredom perception of the participants, it was also observed that there was a statistically significant, positive, and weak correlation between the smartphone addiction and the boredom subscale of the leisure boredom perception.